Characterization of a plasminogen activator from human melanoma cells cultured in vitro - Heussen, Christa; Heussen, Christa (Division of Immunology, 2017)
In this thesis I describe the work that I have done on the isolation and characterization of a plasminogen activator, Mel-PA, that is released by human melanoma cells cultured in vitro. This enzyme was compared to the urinary plasminogen activator, urokinase. The human melanoma cell line, RPMI-7272, (also referred to as the "Bowes" melanoma cell line) released large amounts of Mel-PA into the surrounding medium when cultured under serum-free conditions. A subline of these cells (Bowes II) was developed that was capable of continuous growth in the absence of serum. These cells released only one type of plasminogen activator with a molecular weight of approximately 70 000 daltons. A technique was developed in which plasminogen activators were separated electrophoretically and detected in polyacrylamide gel slabs containing the co-polymerized substrates, plasminogen and gelatin. The technique was compared with the zymographic procedure developed by Granelli-Piperno and Reich (62) using fibrin-plasminogen-agarose underlays. Mel-PA was concentrated and partially purified by affinity chromatography on benzamidine-sepharose. This preparation was used to prepare rabbit antisera to the enzyme. These antibodies inhibited the activity of plasminogen activators released by all melanoma cells but had no effect on urokinase. Antibodies to urokinase had no effect on Mel-PA. A survey of human plasminogen activators and their distribution by immunochemical and electrophoretic techniques showed that tissue extracts and body fluids, with the exception of normal urine, contained mixtures of Mel-PA- and urokinase-type enzymes. Urine of patients with some types of renal disease also contained a Mel-PA type enzyme. A study of the distribution of plasminogen activators in tissues and body fluids obtained from a number of animals showed that all mammals examined had two immunochemically distinct plasminogen activators that corresponded, in their distribution, to the urokinase-like and Mel-PA-like enzymes of man. Antibodies to human Mel-PA cross-reacted with the corresponding enzyme in all mammals tested, whereas antibodies to human urokinase were species specific. The seeds of the South African legume, Erythrina latissima, contain a 20 000 dalton protein that functioned as an inhibitor of Mel-PA, plasmin, and trypsin, but had no effect on urokinase. During its reaction with the enzymes the inhibitor was cleaved by Mel-PA and trypsin but not by urokinase. The susceptible bond was straddled by an intrachain disulphide bridge. The inhibitor bound reversibly to Mel-PA and could therefore be used to develop an affinity reagent for a one-step purification procedure for Mel-PA in melanoma cell harvest fluids. Purified preparations of Mel-PA c0uld be shown to comprise both active enzyme (two chain form) and pro-enzyme (one chain form). The one chain form could be converted to the two-chain form by treatment with plasmin. It could also be shown that fibrinogen and fibrin contained a contaminating protease that was capable of converting pro-Mel-PA to Mel-PA. A comparative study of the kinetic behaviour of Mel-PA and urokinase showed numerous differences between the catalytic activities of these two enzymes. Mel-PA was capable of binding to fibrinogen insolubilized on a plastic surface whereas urokinase did not. The presence of fibrinogen enhanced the plasminogen activating activity of Mel-PA but had no effect on urokinase activity.